Ensifer canadensis sp. nov. strain T173T isolated from Melilotus albus (sweet clover) in Canada possesses recombinant plasmid pT173b harbouring symbiosis and type IV secretion system genes apparently acquired from Ensifer medicae - Bromfield, Eden S. P.; Cloutier, Sylvie; Hynes, Michael F. (Frontiers in Microbiology, 2023)
A bacterial strain, designated T173T, was previously isolated from a root-nodule of a Melilotus albus plant growing in Canada and identified as a novel Ensifer lineage that shared a clade with the non-symbiotic species, Ensifer adhaerens. Strain T173T was also previously found to harbour a symbiosis plasmid and to elicit root-nodules on Medicago and Melilotus species but not fix nitrogen. Here we present data for the genomic and taxonomic description of strain T173T. Phylogenetic analyses including the analysis of whole genome sequences and multiple locus sequence analysis (MLSA) of 53 concatenated ribosome protein subunit (rps) gene sequences confirmed placement of strain T173T in a highly supported lineage distinct from named Ensifer species with E. morelensis Lc04T as the closest relative. The highest digital DNA–DNA hybridization (dDDH) and average nucleotide identity (ANI) values of genome sequences of strain T173T compared with closest relatives (35.7 and 87.9%, respectively) are well below the respective threshold values of 70% and 95–96% for bacterial species circumscription. The genome of strain T173T has a size of 8,094,229 bp with a DNA G + C content of 61.0 mol%. Six replicons were detected: a chromosome (4,051,102 bp) and five plasmids harbouring plasmid replication and segregation (repABC) genes. These plasmids were also found to possess five apparent conjugation systems based on analysis of TraA (relaxase), TrbE/VirB4 (part of the Type IV secretion system (T4SS)) and TraG/VirD4 (coupling protein). Ribosomal RNA operons encoding 16S, 23S, and 5S rRNAs that are usually restricted to bacterial chromosomes were detected on plasmids pT173d and pT173e (946,878 and 1,913,930 bp, respectively) as well as on the chromosome of strain T173T. Moreover, plasmid pT173b (204,278 bp) was found to harbour T4SS and symbiosis genes, including nodulation (nod, noe, nol) and nitrogen fixation (nif, fix) genes that were apparently acquired from E. medicae by horizontal transfer. Data for morphological, physiological and symbiotic characteristics complement the sequence-based characterization of strain T173T. The data presented support the description of a new species for which the name Ensifer canadensis sp. nov. is proposed with strain T173T (= LMG 32374T = HAMBI 3766T) as the species type strain.